A case of MuSK antibody‐positive myasthenia gravis patient mimicking amyotrophic lateral sclerosis with four videofluoroscopic examinations. Issue 1 (16th April 2021) - Kasahara, Takashi; Ikeda, Saori; Koyama, Yuji; Toyokura, Minoru; Masakado, Yoshihisa
Abstract: Anti‐muscle‐specific tyrosine kinase (MuSK) antibody‐positive myasthenia gravis (MG) patients sometimes present with bulbar symptoms such as tongue atrophy, nasal voice, dysarthria, or dysphagia and subsequent progressive weight loss. These symptoms may be confused with those of bulbar‐onset amyotrophic lateral sclerosis (ALS). We performed four videofluoroscopic evaluations and investigated the clinical course of a MuSK‐MG patient before and after administration of intensive immunotherapies.